2012
DOI: 10.1111/j.1470-6431.2012.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer reactions to the availability of organic food in discount supermarkets

Abstract: The market for organic food products in industrial countries has changed significantly. Conventional grocery stores have entered this market in recent years and now present an alternative point of purchase to farmers’ markets and specialized health food shops. In Germany, the main newcomers in this field are the discount supermarkets. The question is whether the increased supply of organic food products leads to sustained effects on consumer behaviour. In other words, can a first‐time purchase of organic produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 49 publications
7
68
0
3
Order By: Relevance
“…The factors that Cypriots use to distinguish organic vegetables from conventional come in high accordance with studies from Germany and Poland (Gottschalk and Leistner, 2013;Bryla, 2016). The latter indicated that consumers are willing to pay higher for organic food (17.4% higher).…”
Section: Discussionsupporting
confidence: 65%
“…The factors that Cypriots use to distinguish organic vegetables from conventional come in high accordance with studies from Germany and Poland (Gottschalk and Leistner, 2013;Bryla, 2016). The latter indicated that consumers are willing to pay higher for organic food (17.4% higher).…”
Section: Discussionsupporting
confidence: 65%
“…Nevertheless, regular consumers also report high prices as a problem (Padel and Foster ; Zanoli and Naspetti ). Exploring this in more detail from the side of organic consumers, studies indicate that high prices are perceived as a disadvantage (Gottschalk and Leistner ), have a negative association (Padel and Foster ; Zanoli and Naspetti ), and are considered temporary rather than permanent barriers (Aschemann‐Witzel and Niebuhr Aagard ).…”
Section: Results and Conclusion Per Research Questionmentioning
confidence: 99%
“…The OOC identified in this study might nevertheless be different from "first time organic buyers" as identified in another study focussing on the question whether discount stores can have an "icebreaker" function to continue organic food consumption. It seems well supported that discount stores contributed to the rising demand in organic food [7]. Only 10% of the OOC prefer discount stores as grocery stores, indicating that the multitude of food choice motives of the OOC are not exclusively fulfilled in the discount stores either.…”
Section: Discussionmentioning
confidence: 95%
“…This study was conducted with the aim of learning more about how occasional organic consumers differ from regular organic consumers, a research question which has rarely been studied [6] [7]. While expected differences were found in the overall picture with conventional consumers showing lowest, OOC medium and ROC the strongest scores on "pro variables" for organic food choices and vice versa for the "contra variables", some particular differences between OOC and ROC emerged that might explain why OOC are reluctant to become ROC: Response scale ranged from 1-agree/important to 5 disagree/not important; a Sum score from 1-no knowledge to 5-high knowledge; The assumption of homogeneity of covariance matrices was violated (Box's test < 0.05); however, since inspection of variances and covariance revealed that the larger group produced greater variances, probability values can be trusted [67], additionally, a non-parametric test was used for the univariate comparison, which confirm stability of test results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation